"There Is a Big Question Mark": Managing Ambiguity in a Moroccan Maternity Ward. (1st April 2019) - Newman, Jess Marie
Abstract: In Morocco, where extramarital sex and abortion are illegal, single mothers' ambiguous status before the law inflects medical decision‐making. Leaky boundaries between the court and the hospital required doctors and administrators to work with multiple forms of documentation while anticipating external surveillance. Gaps between everyday experience and legalized forms of identity created confusion across multiple institutions. When discussing single mothers, hospital staff often spoke of "question marks" that flagged tensions between legibility and liability, disappearance and documentation. Managing question marks ramified surveillance and categorization. Ultimately, however, attempts to administratively resolve single mothers' ambiguity created gaps and inconsistencies that allowed vulnerable patients to disappear from view.